2019
DOI: 10.1002/apj.2347
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of falling film flow characteristics outside shaped tubes related to a spiral‐wound heat exchanger

Abstract: In this paper, the falling film flow and the effects of the marine inclination on the shell-side flow pattern outside the sinusoidal corrugated tube and the square-corrugated tube related to a spiral-wound heat exchanger are experimentally studied using n-pentane as the testing fluid. The flow field phenomenon and the film thickness are investigated with the utilization of high-speed camera technology. The results show that the critical Re of the flow regime transition of the falling film outside the square-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Owing to the small transfer resistance and high transfer efficiency, the falling film has attracted more attention for applications such as desalination, gas treatment, air separation, refrigeration systems, and distillation 1–5 . To guarantee heat and mass transfer efficiency, the surface must be wetted entirely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the small transfer resistance and high transfer efficiency, the falling film has attracted more attention for applications such as desalination, gas treatment, air separation, refrigeration systems, and distillation 1–5 . To guarantee heat and mass transfer efficiency, the surface must be wetted entirely.…”
Section: Introductionmentioning
confidence: 99%
“…The falling film outside the sinusoidal corrugated tube and the square‐corrugated tube were measured using n‐pentane as the testing fluid. It showed that the tube shape has a great influence on the flow regime transition 3 . Ebanesar and Mani 31,32 discovered that corrugated plates of the sinusoidal type contribute to the film heat transfer under the phase change condition.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the heat transfer correlation was verified using a parallel-tube heat transfer test bench with air as the working fluid. Liu et al [ 6 ] proposed a mathematical model for a double-layer spiral-wound heat exchanger and experimentally verified the accuracy of the theoretical model. Neeraas et al [ 7 ] conducted an experimental analysis of the falling-film characteristics of the shell side of a tubular heat exchanger, and compared the results with the calculation method for the heat transfer coefficient proposed by Bays and McAdams [ 8 ].…”
Section: Introductionmentioning
confidence: 99%